Globalization challenged : conviction, conflict, community - Rupp, George (University seminars/Leonard Hastings Schoff memorial lectures., 2006)
In Globalization Challenged, George Rupp, president of the International Rescue Committee, outlines the steps necessary to engage the contemporary conflict between traditional religious belief and Western secularism. According to Rupp, the key objective is to build a community that is inclusive without denying the validity of particular commitments. While he acknowledges the threat of ""resurgent fundamentalism, "" Rupp also criticizes secularists who fail to recognize or acknowledge the role of religion and its ideological equivalents in influencing public policy. All vie.